The Influence Of External Factors And Internal Factors On Stock Prices In The Property Sector For The 2013-2023 Period On The Indonesian Stock Exchange - I Putu Risky Dharma Putra Tenaya; Ign Oka Widana; Gunardi Endro (Sean Institute, 2024)
This study analyzes the effect of external factors, such as interest rates, property capitalization value, and house price index, as well as internal factors such as the value of DER (Debt Equity Ratio), ROA (Return on Assets), and NPM (Net Profit Margin), on the price of property stocks on the Indonesia Stock Exchange (IDX) during the period 2013-2023. In this study, the population in this study were property stocks totaling 85 issuers of shares that were sloping on the Indonesia Stock Exchange. And in this study to determine the sample to be used, the researchers used the simple random sampling method. The method in this study uses quantitative methods with simple random sampling techniques. In this case the sample to be used is as many as 20 samples of property stocks listed on the IDX for the period 2013-2023. The data used is secondary data in the form of financial statements. the analysis used is descriptive statistical analysis technique, time series method, multiple linear regression analysis, classical assumption test, Multivariate Test using SPSS. The results showed, ROA, DER, house price index and interest rates had a positive and significant effect on property stock prices for the period 2013-2023 while the capitalization value of the property had no significant effect on stock prices. The negative coefficient direction explains that an increase in market capitalization will result in a decrease in stock prices on the IDX for the 2013-2023 period. The results of this study show an Rsquare value of 0.580 or 58% of the influence of the independent variable (x) on the dependent variable (y) while 42% of the stock price can be explained by other variables. The implication is that investors and market participants can consider information about relevant external and internal factors in the property market. This research provides important contributions and contributions in understanding the dynamics of the property stock market in Indonesia and can be a reference for further researchers in this field.